2002
DOI: 10.5597/lajam00018
|View full text |Cite
|
Sign up to set email alerts
|

Size and shape variability in the skull of <i>Pontoporia blainvillei</i> (Cetacea: Pontoporiidae) from the Brazilian coast

Abstract: The existence of sexual dimorphism in Pontoporia blainvillei has long been known, with females being larger than males. However, no study so far has explored this dimorphism separately in its size and shape components. Here we analyse sexual dimorphism present in eight linear measurements of the skulls of 56 specimens (30 females and 26 males) of P. blainvillei from several localities along the Brazilian coast. We also investigate the sexual dimorphism in size and shape using geometric morphometric techniques,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 7 publications
2
17
1
1
Order By: Relevance
“…There is not much evidence that this may be a sexually dimorphic character. In P. blainvillei, it has been observed that the female has a larger size (reflected in the size of skull and teeth- Higa et al 2002;Ramos et al 2000b) but there are no known cases in odontocetes that have demonstrated differences in the size of the rostrum as a sexually dimorphic character. Additionally, a long or short rostrum could be interpreted to imply different feeding habits (Werth 2006), but still these inferences are difficult to delimit in living species and may be less crucial in the animal's life than has been generally thought.…”
Section: Discussionmentioning
confidence: 97%
“…There is not much evidence that this may be a sexually dimorphic character. In P. blainvillei, it has been observed that the female has a larger size (reflected in the size of skull and teeth- Higa et al 2002;Ramos et al 2000b) but there are no known cases in odontocetes that have demonstrated differences in the size of the rostrum as a sexually dimorphic character. Additionally, a long or short rostrum could be interpreted to imply different feeding habits (Werth 2006), but still these inferences are difficult to delimit in living species and may be less crucial in the animal's life than has been generally thought.…”
Section: Discussionmentioning
confidence: 97%
“…However, it is commonly and erroneously believed that the species was described in Gervais and d'Orbigny (1844b) (e.g. Pinedo et al, 1989;Higa et al, 2002). The reason for the confusion lies in the fact that the publication date of Gervais and d'Orbigny (1844b) (27 April 1844), corresponds to the date of the session of the Société Philomatique but not to the date of its actual publication (see Mones and Philippi, 1992).…”
Section: Historical Review Of Franciscana Colourationmentioning
confidence: 99%
“…Fortunately other approaches including morphological and molecular analyses have been used successfully for determining stock units (e.g. Pinedo, 1991;Secchi et al, 1998;Higa et al, 2002;Ramos et al, 2002;Secchi et al, 2003;Lázaro et al, 2004).…”
Section: Final Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of the mammals of Santa Catarina State, Cherem et al (2004) indicated that the species occurs along the coast of the whole state. Opportunistic sightings (FLORES, 2009), studies related to biological information, such as diet , and comparative studies related to morphology (HIGA et al, 2002) and contamination TORRE et al, 2012) are reported in the literature.…”
Section: Introductionmentioning
confidence: 99%